"You're the best around": an argument for playoffs and tournaments. Issue 2 (3rd May 2016) - Harper, Aaron
Abstract: Recent articles, including those by Dixon and Torres and Hager, criticize tournament playoffs, primarily for reasons of fairness and integrity. Many suggest that playoff and tournament prominence reflect monetary and entertainment interests rather than the pursuit of athletic excellence. Nevertheless, tournament playoffs are increasingly popular. While the concerns are serious, in this paper I defend the overlooked value of playoffs and tournaments. Playoff critics employ too narrow a conception of the best team and too limited a view of excellence. Rather, playoffs and seasons highlight distinct and valuable conceptions of athletic excellence. To better capture this, I consider two alternative championship formats: the hybrid system and championship pluralism. The hybrid system includes a playoff informed by the regular season. Despite its apparent advantages, I reject the hybrid approach. Instead, I propose championship pluralism as a preferred championship model.